Determinations of the financial strategy of Malaysian banks which practise interest free schemes. case study: Bank Islam Malaysia Berhad (BIMB) / Azizah Hj. Dollah, Asmah Hj. Zainuddin and Rahimah HP Shawkataly - Hj. Dollah, Azizah; Hj. Zainuddin, Asmah; HP Shawkataly, Rahimah (Research Management Institute (RMI), 1995)
This study examines the importance of Islamic banks in Malaysia as an institution which offers interest-free scheme. The study revealed that there are interactions between environmental determinants and financial strategies of Bank Islam Malaysia Berhad (BIMB). The model proved that before the adoption of the interest-free scheme by conventional banks in Malaysia, BIMB enjoyed high strategic choice and low environmental determinism. However, at the early stage of the adoption of interest-free scheme, BIMB faced high environmental determinism and low strategic choice. When all title conventional banks in Malaysia adopted interest-free scheme as one of their products, BIMB faced high environmental determinism and high strategic choice.